2021
DOI: 10.5194/acp-21-16817-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ice number concentrations in contrails from low-aromatic biofuel blends

Abstract: Abstract. Sustainable aviation fuels can reduce contrail ice numbers and radiative forcing by contrail cirrus. We measured apparent ice emission indices for fuels with varying aromatic content at altitude ranges of 9.1–9.8 and 11.4–11.6 km. Measurement data were collected during the ECLIF II/NDMAX flight experiment in January 2018. The fuels varied in both aromatic quantity and type. Between a sustainable aviation fuel blend and a reference fuel Jet A-1, a maximum reduction in apparent ice emission indices of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Under "soot-poor" conditions, ice crystal numbers are thought to be constrained by a lower limit of around 10 13 kg −1 due to the presence of organic particles and ambient natural aerosols (Kärcher, 2018). Recent cruise measurements have found that the fraction of aircraft nvPM that activates into contrail ice crystals depends on the ambient temperature (Bräuer et al, 2021a), and they also confirmed that a lower EI n reduces the ice crystal number and optical depth (τ contrail ) of young contrails (Voigt et al, 2021;Bräuer et al, 2021b). Studies that used a contrail life cycle simulation have shown that a lower nvPM EI n can reduce contrail lifetime and climate forcing (Burkhardt et al, 2018;Teoh et al, 2020b;Bock and Burkhardt, 2019;.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Under "soot-poor" conditions, ice crystal numbers are thought to be constrained by a lower limit of around 10 13 kg −1 due to the presence of organic particles and ambient natural aerosols (Kärcher, 2018). Recent cruise measurements have found that the fraction of aircraft nvPM that activates into contrail ice crystals depends on the ambient temperature (Bräuer et al, 2021a), and they also confirmed that a lower EI n reduces the ice crystal number and optical depth (τ contrail ) of young contrails (Voigt et al, 2021;Bräuer et al, 2021b). Studies that used a contrail life cycle simulation have shown that a lower nvPM EI n can reduce contrail lifetime and climate forcing (Burkhardt et al, 2018;Teoh et al, 2020b;Bock and Burkhardt, 2019;.…”
Section: Introductionmentioning
confidence: 95%
“…While atmospheric conditions determine the formation and persistence of a contrail, the aircraft non-volatile soot number emissions index (EI n ) modifies the contrail properties (Kärcher, 2018;Schumann, 1996;Voigt et al, 2021;Bräuer et al, 2021b). In the "soot-rich" regime, where EI n > 10 13 kg −1 , and under ice supersaturated conditions, the initial contrail ice crystal number is proportional to nvPM EI n because these particles act as the primary source of condensation nuclei (Schumann, 1996;Kleine et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The first key parameter is the soot emission indices that are directly linked to the engine and fuel characteristics as shown by [77]. Although current ongoing projects such as SENECA plan to use a classical current type of fuel such as Jet-A1, the fuel choice and the combustion technology will be key in the determination of the soot emission index that will affect the ice crystal distribution characterizing the contrails and their climate effect.…”
Section: Formation Of Contrails and Contrail Cirrusmentioning
confidence: 99%
“…The RF and ERF are normally defined as global mean values and are usually adjusted to stratospheric equilibrium, while the EF contrail uses the local and instantaneous RF values (change in radiative flux per contrail area) and estimates the total climate forcing from individual contrail segment or flights. The global annual mean contrail cirrus net RF (111 [33,189] mW m −2 , 95% confidence interval) and ERF (57 [17,98] mW m −2 ) in 2018 could exceed that of the forcing from aviation's cumulative CO 2 emissions since its inception (RF and ERF of ~34 [28,40] mW m −2 ) [1], and a recent study found significant interannual variability in the annual mean contrail cirrus net RF over the North Atlantic (204-280 mW m −2 ) [21].…”
Section: State-of-the-art: Contrail Impacts and Mitigationmentioning
confidence: 99%
“…To reduce the contrail climate forcing, mitigation solutions could be targeted at those flights which produce persistent warming contrails including: (i) the use of sustainable alternative fuel, which reduces nvPM particles, contrail optical depth, and RF [31][32][33] (but supply remains severely constrained at the present day [34,35]); or (ii) flight-diversion strategies that minimize the formation of strongly warming contrails [30,36]. We note that solution (ii) does not require the avoidance of all contrails because ~70% of contrails formed over the North Atlantic are short-lived with negligible radiative significance, and ~20% of persistent contrails have a net cooling effect [21].…”
Section: State-of-the-art: Contrail Impacts and Mitigationmentioning
confidence: 99%